Comparative Study of Thigh Muscles and Bones Conformation and Some Carcass Traits of Local vs. Imported Turkey Strain - Taha, N.T.; Farran, M.T. (International Journal of Poultry Science, 2009)
Four males and four females of each of imported BUT-9 and local strain of turkey were slaughtered at marketing age, to study live body weight, som carcass traits, in addition to drumstick’s bones at Tibia region “Nazarian bones2” which radiography and chemically analyzed for fat-free bone parameters. The results indicated that BUT-9 revealed higher (p<0.05) live body weight, ready to cook carcass weight percent (dressing percent), breast weight and percent, left drum-stick weight and percent as compared with local strain of turkey. BUT-9 strain also significantly (p<0.05) had more number of drum-stick’s muscles, tibia weight and width, drum-stick’s thickness and width and drum-stick’s bones percent. However, local strain had significantly (p<0.05) more drumsticks bones “Nazarian bones” while BUT-9 had no Nazarian bones in their drum-stick’s muscles. Males had more (p<0.05) live body weight, neck, drum-stick’s width, length and tibia length, breast weight, width and depth and shank weight as a percent of live body weight. As compared with fibula there were no significant differences between those bones and fibula for dry matter, phosphorus and magnesium percents, while a significant (p<0.05) differences were noticed for ash and calcium. But fat percent didn’t show any significant differences between Nazarian bones themselves but were noticed with fibula. Sex had no significant effect on bone parameters except for males turkey bones which had more (p<0.05) dry matter than females.